Perbandingan Kurikulum Pendidikan Karakter Indonesia Dan Finlandia: Implikasi Bagi Pengembangan Karakter Siswa - Kurnia Sofiani, Ika; Yuniarti, Isma; Suhaila, Putri; Tri Agustina, Karina (Jurnal Al-Kifayah: Ilmu Tarbiyah dan Keguruan, 2025)
Character education is a fundamental aspect in forming a generation that is not only intellectually superior, but also morally and socially mature. In a dynamic global context, character education is key to preparing individuals with integrity, critical thinking, and responsibility. This study aims to compare the character education curriculum in Indonesia and Finland in order to identify effective practices that can be applied in Indonesia. The benefit of this study is to provide strategic recommendations for the development of more contextual, inclusive, and sustainable character education policies and practices. The method used is qualitative with a comparative study approach, involving the study of policy documentation, official curricula, and interviews with education practitioners from both countries. The results of the study show that although both countries prioritize character education, their approaches differ significantly. Indonesia tends to apply a normative and administrative top-down approach, while Finland integrates character education organically into school life, with an emphasis on student well-being, teacher autonomy, and community involvement. The conclusion of this study confirms that Indonesia can take inspiration from the Finnish system, not by imitating it in its entirety, but by adapting these good practices to the local context to form a living, participatory, and impactful character education culture